The role of big data in addressing the tobacco fiscal paradox in Indonesia: A literature review and descriptive analysis of policy oversight effectiveness - Sitompul, Jhonriz Steven (Institute for Advanced Science Social, and Sustainable Future, 2025)
Background: The structure of the goods and services market in Indonesia cannot be separated from tobacco or cigarette commodities. In everyday life, households as consumers often include cigarettes—tobacco’s primary output—among their essential utilities, alongside food, clothing, and shelter, all of which are closely linked to household income. This situation gives rise to a paradox, particularly in light of the fiscal allocation to sectors other than health. Therefore, this study aims to analyze the literature and provide a descriptive review of the use of big data and the structure of the tobacco commodity market in order to identify effective fiscal policies for tobacco products. Methods: This study utilizes secondary data, including: (i) literature articles and legal or regulatory documents; (ii) data from Statistics Indonesia/Badan Pusat Statistik (BPS); (iii) the national and regional government budgets; (iv) World Development Indicators; and (v) our world in data by Oxford University. The research design focuses on Indonesia as the primary unit of analysis at the national level, which is then compared with other countries to generate a research synthesis through a literature review. This is further supported by descriptive analysis that serves as the basis for policy recommendations. Findings: The study reveals three main findings. First, there is a critical need to improve education, financial literacy, and digital literacy among the population. Second, strengthening public trust in government institutions is essential in order to increase state revenue. Lastly, the government’s utilization of digital technologies and big data plays a significant role in enhancing governance and policy effectiveness. Conclusion: The core issue identified in this study can be summarized as the need to address cross-budgeting challenges through innovations such as the use of facial recognition technology powered by big data to identify smokers. Novelty/Originality of this article: This study employs both theoretical and empirical literature, supported by descriptive analysis.